PENERAPAN KURIKULUM PERPAJAKAN PADA TINGKAT SMA DALAM UPAYA MENINGKATKAN KESADARAN WAJIB PAJAK - Santoso, Dasul (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
Tax awareness and compliance by taxpayers in reporting and paying theirtaxes correctly is an important issue for a country, considering that taxes are one ofthe largest revenues for the state. The discussion in this paper focuses onfundamental questions about the role of formal education in character building ontaxpayer awareness which is carried out through matriculation at the senior highschool level. To answer this question, the authors use the doctrinal research methodby taking a conceptual approach and the applicable laws and regulations. The resultsof the writing describe that formal taxation education in high school has a veryimportant role in building the character and awareness of taxpayers in paying taxes.